Introducing COMEPELDA: Comprehensive European Parliament electoral data covering rules, parties and candidates. (June 2022) - Däubler, Thomas; Chiru, Mihail; Hermansen, Silje SL
We introduce a new collection of data that consolidates information on European Parliament elections into one comprehensive source. It provides information on formal electoral rules as well as national-level and district-level election results for parties and individual politicians (including full candidate lists). The use of existing and new key variables makes it easy to link the data across the different units of observation (country, party, candidate, member of parliament) and join them with external information. Currently, the data cover four elections (1999–2014). Among other aspects, the collection should facilitate research on the European Parliament's allegedly weak electoral connection. In this article, we outline the main features of the datasets, describe patterns of intra-party competition and preference voting and conduct exploratory analyses of individual-level changes in list positions.